Light Stimulates a Transducin-Independent Increase of Cytoplasmic Ca(2+) and Suppression of Current in Cones from the Zebrafish Mutant nof - Brockerhoff, Susan E. (J Neurosci, 2003)
Transducins couple visual pigments to cGMP hydrolysis, the only recognized phototransduction pathway in vertebrate photoreceptors. Here we describe a zebrafish mutant, no optokinetic response f(w21) (nof), with a nonsense mutation in the gene encoding the α subunit of cone transducin. Retinal morphology and levels of phototransduction enzymes are normal in nof retinas, but cone transducin is undetectable. Dark current in nof cones is also normal, but it is insensitive to moderate intensity light. Thenof cones do respond, however, to bright light. These responses are produced by a light-stimulated, but transducin-independent, release of Ca(2+) into the cone cytoplasm. Thus, in addition to stimulating transducin, light also independently induces release of Ca(2+) into the photoreceptor cytoplasm.